The helpfulness of reflecting teams in family therapy. Issue 4 (17th December 2020) - Hicks, Stephanie; Kustner, Claudia; Constable, Chloe
Abstract : Reflecting teams (RTs) are used in family therapy in order to introduce multiple perspectives and provide the 'difference that makes a difference'. Research suggests that reflections made by an RT may be a factor in the change process for family members. This study aims to further the understanding of the helpfulness of reflections in family therapy, thus supporting RTs to be as effective as possible. A quantitative longitudinal questionnaire method was used in order to collect data on family members' perceptions of the helpfulness of reflections made by an RT during their family therapy sessions. The results show that certain types of reflections are less helpful than others and the helpfulness of reflections was found to contribute to the change process for family members. The results are discussed along with reflections on the research process, limitations and recommendations for further research. Practitioner points: Some types of reflections made by the reflecting team are more helpful than others, so using these more helpful reflection types may optimise progress in family therapy Reflections contribute to the change process in family therapy, therefore reflecting teams are valuable to include in family therapy sessions Abstract : 反思小组在家庭治疗中的作用: 反思小组（RTs）被用于家庭治疗，目的是引入多个视角，并提供"产生影响的不同因素"。研究表明，RT所进行的反思可能是家庭成员改变过程中的一个因素。本研究旨在进一步了解反思在家庭治疗中的作用，从而支持RTs尽可能发挥作用。研究者采用定量纵向问卷调查的方法，收集家庭成员对家庭治疗过程中RT反思效果的看法。研究结果显示，某些类型的反思对家庭成员的影响不如另一些类型的反思，并且有益的反思对家庭成员的变化过程有贡献。文中对研究结果进行了讨论，并对研究过程、局限性和进一步研究提出了建议。 对从业者的启示: 反思小组做出的某些类型的反思比其他类型的反思更有帮助，因此使用这些更有帮助的反思类型可以优化家庭治疗的进展 反思有助于家庭治疗的变化过程，因此反思团队在家庭治疗会面中是很有价值的组成部分 Abstract : La utilidad de los equipos reflexivos en la terapia familiar: Los equipos reflexivos (ER) se utilizan en la terapia familiar para introducir múltiples perspectivas y proporcionar una "diferencia que marca la diferencia". La investigación sugiere que las reflexiones hechas por un ER pueden ser un factor en el proceso de cambio para los miembros de la familia. Este estudio tiene como objetivo profundizar en la comprensión de la utilidad de las reflexiones en la terapia familiar, apoyando así a los ER para que sean lo más efectivos posible. Se utilizó un método de cuestionario longitudinal cuantitativo para recopilar datos sobre las percepciones de los miembros de la familia acerca de la utilidad de las reflexiones hechas por un ER durante sus sesiones de terapia familiar. Los resultados muestran que ciertos tipos de reflexiones son menos útiles que otras y se encontró que la utilidad de las reflexiones contribuye al proceso de cambio para los miembros de la familia. Los resultados se discuten junto con reflexiones sobre el proceso de investigación, limitaciones y recomendaciones para futuras investigaciones. Puntos de implicación práctica: Algunos tipos de reflexiones hechas por el equipo reflexivo son más útiles que otros, por lo que el uso de estos tipos de reflexión más útiles puede optimizar progreso en la terapia familiar Las reflexiones contribuyen al proceso de cambio en la terapia familiar, por lo tanto, los equipos reflexivos son valiosos para incluirlos en las sesiones de terapia familiar.